치위생과 졸업예정자의 직업의식과 취업가치관에 대한 조사연구 - 장성연; Sung Yeon Jang (Chiwisaeng gwahakoeji, 2015)
This study has an objective not only to be helpful to the understanding about students. career and employment preparation by investigating the present conditions which are related with vocational consciousness and job values of dental hygiene department graduating students. Study subjects were 350 female graduating students in 3-year-course College, dental hygiene department at five areas of Seoul, Gyeonggi, Gangwon and Gyeongnam. Data were analyzed using IBM SPSS Statistics ver. 19.0. Regarding job values, job prospect of dental hygienist is a little developmental (55.2%) and institution hoping to work is dental clinic (43.2%), reasons for employment in major area are good wage and working environment (24.0%). And regarding opinion about job, dental hygienist job is a measure for living income (69.7%). Regarding job selection conditions, 35.0% subjects replied good human relationship. In the questionnaires regarding professional job in vocational consciousness category, results showed high percentages in that .the occupation is a job in charge of oral health improvement.; regarding academic area, .scaling should be done better than dentist.; regarding human relationship, .harmony between colleagues is closely related with job efficiency.; regarding work ethics, .development of dental hospital (clinic) and dental hygienist is correlated.. In vocational consciousness of study subjects, higher major satisfaction showed significant differences in professional job consciousness and work ethics consciousness (p＜0.05) and the correlation results in vocational consciousness areas showed all statistically significant correlations (p＜0.01). In case that the characteristic in one type is higher among 4 types, all other types showed high characteristics and also showed high general vocational consciousness.